2022
DOI: 10.1093/hr/uhac190
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction in non-climacteric fruit ripening

Abstract: Fleshy fruit ripening involves changes in numerous cellular processes and metabolic pathways, resulting from the coordinated actions of diverse classes of structural and regulatory proteins. These include enzymes, transporters and complex signal transduction systems. Many aspects of the signaling machinery that orchestrates the ripening of climacteric fruits, such as tomato (Solanum lycopersicum), have been elucidated, but less is known about analogous processes in non-climacteric fruits. The latter include st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 138 publications
0
6
0
Order By: Relevance
“…It has been well-documented that the ABA signaling pathway plays a central role in non-climacteric fruit ripening, including strawberry, grape and sweet cherry [63,64]. Multiple lines of evidence have shown that ethylene and ABA worked in synergy during non-climacteric fruit ripening; ethylene signaling could be involved in adjusting nonclimacteric fruit ripening by merging into the ABA signaling pathway [20,21,44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-documented that the ABA signaling pathway plays a central role in non-climacteric fruit ripening, including strawberry, grape and sweet cherry [63,64]. Multiple lines of evidence have shown that ethylene and ABA worked in synergy during non-climacteric fruit ripening; ethylene signaling could be involved in adjusting nonclimacteric fruit ripening by merging into the ABA signaling pathway [20,21,44].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional regulation is largely determined by transcription factors (TFs), whereas post-transcriptional regulation is achieved by the group modification of the topological structure, which may result in changes in many protein behaviors, such as activity, stability and cellular localization [ 3 , 9 , 10 ]. Protein kinase/phosphatase-catalyzed reversible phosphorylation has been established to be the major mechanism of protein modification and therefore plays a pivotal role in cellular signal transduction [ 11 , 12 ]. In recent decades, extensive efforts have been made to explore the transcriptional regulation mechanisms of cellular metabolisms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, extensive efforts have been made to explore the transcriptional regulation mechanisms of cellular metabolisms. Although a large number of TFs together with their target genes have been identified to be involved in specific metabolic systems, the profound signaling mechanisms upstream of TFs remain largely elusive [ 12 ]. In recent years, explorations into the mechanisms of signal transduction in fruit ripening have attracted the attention of plant scientists.…”
Section: Introductionmentioning
confidence: 99%
“…The phytohormone abscisic acid (ABA) can play either a dominant or supportive role in modulating non-climacteric and climacteric fruit ripening, respectively ( Kou et al., 2021a ). Although many studies have reported that the ABA controls non-climacteric fruit ripening and influence fruit quality traits ( Kou et al., 2021b ; Li et al., 2022a ), there is limited understanding of this process compared with that of ethylene in climacteric fruit ( Wang et al., 2022a ). Better elucidation of mechanisms of ABA-mediated fruit ripening has considerable potential for enhancing our understanding of both climacteric and non-climacteric ripening and for developing novel traits and varieties, especially concerning non-climacteric fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple phytohormone signaling genes participating in strawberry ripening regulated by ABA have been documented ( Gu et al., 2019 ; Fenn & Giovannoni, 2021 ; Wang et al., 2022a ), and ABA can act synergistically or antagonistically with auxin, gibberellins (GAs), ethylene, and jasmonic acids (JAs) in strawberry ( Li et al., 2022a ). In addition, the roles of ABA signaling genes in ripening, including FaPYR1 ( Pyrabactin resistance 1 ; Chai et al., 2011 ), FaABI1 ( ABSCISIC ACID-INSENSITIVE 1 encoding a PP2C protein; Jia et al., 2013b ), FaSnRK2.6 ( SNF1-related protein kinase 2.6 ; Han et al., 2015 ), and FaABAR ( Magnesium-protoporphyrin IX chelatase H subunit ; Jia et al., 2011 ), have been well characterized.…”
Section: Introductionmentioning
confidence: 99%